2015
DOI: 10.1523/jneurosci.5109-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

A Human Monoclonal IgG That Binds Aβ Assemblies and Diverse Amyloids Exhibits Anti-Amyloid ActivitiesIn VitroandIn Vivo

Abstract: Alzheimer's disease (AD) and familial Danish dementia (FDD) are degenerative neurological diseases characterized by amyloid pathology. Normal human sera contain IgG antibodies that specifically bind diverse preamyloid and amyloid proteins and have shown therapeutic potential in vitro and in vivo. We cloned one of these antibodies, 3H3, from memory B cells of a healthy individual using a hybridoma method. 3H3 is an affinity-matured IgG that binds a pan-amyloid epitope, recognizing both A␤ and Ig light chain (LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 64 publications
2
16
0
Order By: Relevance
“…The most straightforward strategies have aimed at directly inhibiting the production of neurotoxic species of amyloid, either via viral vector expression of Aβ degrading enzymes, such as Neprilysin (Li et al, 2015; Lebson et al, 2010), or anti-Aβ single-chain antibodies to achieve passive immunization (Levites et al, 2015). Alternatively, targeting the cleavage of APP has been attempted, with genetic transfer of siRNA specific for β-secretase (Nawrot, 2004) or shRNA to knock-down the orphan G protein-coupled receptor that regulates activity of γ-secretase (Huang et al, 2015a), the first and second enzymes, respectively, controlling the proteolysis of APP to produce the neurotoxic amyloid peptides, respectively.…”
Section: Different Modalities For Different Diseasesmentioning
confidence: 99%
“…The most straightforward strategies have aimed at directly inhibiting the production of neurotoxic species of amyloid, either via viral vector expression of Aβ degrading enzymes, such as Neprilysin (Li et al, 2015; Lebson et al, 2010), or anti-Aβ single-chain antibodies to achieve passive immunization (Levites et al, 2015). Alternatively, targeting the cleavage of APP has been attempted, with genetic transfer of siRNA specific for β-secretase (Nawrot, 2004) or shRNA to knock-down the orphan G protein-coupled receptor that regulates activity of γ-secretase (Huang et al, 2015a), the first and second enzymes, respectively, controlling the proteolysis of APP to produce the neurotoxic amyloid peptides, respectively.…”
Section: Different Modalities For Different Diseasesmentioning
confidence: 99%
“…3H3 inhibits the fibrillization of curli. We previously observed that 3H3 inhibits polymerization of amyloid fibrils from Aβ and a lambda immunoglobulin associated with primary amyloidosis 38 .…”
Section: Resultsmentioning
confidence: 99%
“…Amyloid proteins with highly divergent sequences can share conformational epitopes that are recognizable by mAbs 49,50 . Some mAbs that bind pan-amyloid epitopes inhibit fibrillization of eukaryotic amyloids and have anti-amyloid activities in vivo 38,49,51,52 , but this has not been shown for prokaryotic amyloids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations